2022
DOI: 10.7759/cureus.30485
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antiresorptive Drug Holidays on Medication-Related Osteonecrosis of the Jaw: A Systematic Review and Meta-Analysis

Abstract: The objective of this study is to evaluate the effectiveness of discontinuing high-dose antiresorptive (AR) therapy in reducing the risk of medication-related osteonecrosis of the jaw (MRONJ) in patients treated with AR medications and undergoing dentoalveolar surgery or tooth extractions.The review was carried out in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations. A literature search was conducted using the databases MEDLINE, Embase, Web of Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Complementing these findings, another study systematically reviewed the literature, including both observational and interventional studies, to assess the effect of an AR drug holiday on the development of MRONJ. This extensive analysis encompassed 6808 subjects, comparing cases from the drug holiday group with controls from the non-drug holiday group [22]. The results revealed no significant difference between the groups in the development of MRONJ, leading to the conclusion that AR drug holidays do not minimize the risk of MRONJ, and their recommendation as a preventive measure is not substantiated by the current evidence [22].…”
Section: The Effectiveness Of Drug Holidaymentioning
confidence: 95%
See 1 more Smart Citation
“…Complementing these findings, another study systematically reviewed the literature, including both observational and interventional studies, to assess the effect of an AR drug holiday on the development of MRONJ. This extensive analysis encompassed 6808 subjects, comparing cases from the drug holiday group with controls from the non-drug holiday group [22]. The results revealed no significant difference between the groups in the development of MRONJ, leading to the conclusion that AR drug holidays do not minimize the risk of MRONJ, and their recommendation as a preventive measure is not substantiated by the current evidence [22].…”
Section: The Effectiveness Of Drug Holidaymentioning
confidence: 95%
“…This extensive analysis encompassed 6808 subjects, comparing cases from the drug holiday group with controls from the non-drug holiday group [22]. The results revealed no significant difference between the groups in the development of MRONJ, leading to the conclusion that AR drug holidays do not minimize the risk of MRONJ, and their recommendation as a preventive measure is not substantiated by the current evidence [22].…”
Section: The Effectiveness Of Drug Holidaymentioning
confidence: 95%
“…Complementing these findings, another study systematically reviewed the literature, including both observational and interventional studies, to assess the effect of an AR drug holiday on the development of MRONJ. This extensive analysis encompassed 6808 subjects, comparing cases from the drug holiday group with controls from the non-drug holiday group [52]. The results revealed no significant difference between the groups in the development of MRONJ, leading to the conclusion that AR drug holidays do not minimize the risk of MRONJ, and their recommendation as a preventive measure is not substantiated by the current evidence [52].…”
Section: The Effectiveness Of Drug Holidaymentioning
confidence: 95%
“…This extensive analysis encompassed 6808 subjects, comparing cases from the drug holiday group with controls from the non-drug holiday group [52]. The results revealed no significant difference between the groups in the development of MRONJ, leading to the conclusion that AR drug holidays do not minimize the risk of MRONJ, and their recommendation as a preventive measure is not substantiated by the current evidence [52].…”
Section: The Effectiveness Of Drug Holidaymentioning
confidence: 95%
“…However, a recent meta-analysis conducted by Aboalela et al (2022) [ 20 ] analyzed eight articles with 6808 subjects and concluded that there was no significant difference in the development of BRONJ following a tooth extraction procedure between the drug holiday group and the non-drug holiday group. The study concluded that drug holidays with antiresorptive (AR) medications will not minimize the risk of BRONJ and cannot be advised based on the available evidence.…”
Section: Reviewmentioning
confidence: 99%